Patrolling Public Areas under Extreme Warm and Extreme Cold Weather Conditions, Protecting Police Personnel, Civilian Populace, Service Animals and Technical Equipment - Papp, Dávid (Magyar Rendészet, 2021)
Nowadays in the extreme weather conditions accompanying the climate change caused by global warming, it has become a challenge to perform patrolling in public areas. Since patrolling public areas must be carried out regardless of the weather conditions, in my paper I intend to describe and review the police tasks in relation to protection against extreme hot and cold weather together with their consequences. In addition to reviewing the current statutory rules and regulations, I formulate proposals to be used during adaptation to inclement weather conditions.